2021
DOI: 10.1101/2021.01.29.21250592
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hot days and Covid-19 – unusual heat stress for nursing professions in Germany

Abstract: ObjectivesOur aim was to identify whether working during hot days alongside with Covid-19 related personal protective equipment causes heat stress for nursing professionals in Germany.MethodsUsing an online survey, we assessed the impact of hot weather on nursing staff performing in personal protective equipment. A random selection of nursing staff from hospitals, nursing homes and outpatient care participated in the survey.ResultsOut of 428 participants, 6.3% were between 16 and 25 years old, 22.8% between 26… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…This is a real concern for the assessment of the thermal stress associated with personal protective equipment among workers, too. Results of this survey confirmed a strong impact of COVID-19 s PPE in the heat stress perception of HCW, in line with the results obtained from similar studies carried out in England [27], in Germany [33], in Asia [6] but also in studies with wider participation [28]. The PCA identified 3 fundamental issues that represent the key elements on which to intervene in the management of the risk related to thermal stress in the health care sector:…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This is a real concern for the assessment of the thermal stress associated with personal protective equipment among workers, too. Results of this survey confirmed a strong impact of COVID-19 s PPE in the heat stress perception of HCW, in line with the results obtained from similar studies carried out in England [27], in Germany [33], in Asia [6] but also in studies with wider participation [28]. The PCA identified 3 fundamental issues that represent the key elements on which to intervene in the management of the risk related to thermal stress in the health care sector:…”
Section: Discussionsupporting
confidence: 82%
“…This aspect is certainly linked to the use of PPE for a high number of hours per day, as confirmed by Lee et al [6] in two Asian countries, and which also determines important heat-related symptoms such as thirst, excessive sweating, fatigue, headache, difficulty concentrating, skin reactions and general discomfort conditions, with potential important effects on both the health and productivity of HCW. Some studies also described dark-colored urine, dizziness, muscle or abdominal cramps, gastrointestinal disturbance, rapid heartbeat [27] and mental symptoms [33] as phenomena associated with the use of PPE. Tabah et al [28] showed that adverse effects of PPE (headaches, thirst and exhaustion) were associated with longer shift durations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation